Soluble NSF attachment protein receptor molecular mimicry by a Legionella pneumophila Dot/Icm effector - King, Nathan P; Newton, Patrice; Schuelein, Ralf; Brown, Darren L; Petru, Marketa; Zarsky, Vojtech; Dolezal, Pavel; Luo, Lin; Bugarcic, Andrea; Stanley, Amanda C; Murray, Rachael Z; Collins, Brett M; et al. (Cellular microbiology, 2015)
Upon infection, Legionella pneumophila uses the Dot/Icm type IV secretion system to translocate effector proteins from the Legionella-containing vacuole (LCV) into the host cell cytoplasm. The effectors target a wide array of host cellular processes that aid LCV biogenesis, including the manipulation of membrane trafficking. In this study, we used a hidden Markov model screen to identify two novel, non-eukaryotic soluble NSF attachment protein receptor (SNARE) homologs: the bacterial Legionella SNARE effector A (LseA) and viral SNARE homolog A proteins. We characterized LseA as a Dot/Icm effector of L. pneumophila, which has close homology to the Qc-SNARE subfamily. The lseA gene was present in multiple sequenced L. pneumophila strains including Corby and was well distributed among L. pneumophila clinical and environmental isolates. Employing a variety of biochemical, cell biological and microbiological techniques, we found that farnesylated LseA localized to membranes associated with the Golgi complex in mammalian cells and LseA interacted with a subset of Qa-, Qb- and R-SNAREs in host cells. Our results suggested that LseA acts as a SNARE protein and has the potential to regulate or mediate membrane fusion events in Golgi-associated pathways.
Keywords: sekvenční homologie aminokyselin; buněčné linie; lidé; interakce hostitele a patogenu; makrofágy; Virulence Factors; Cell Line; Legionella pneumophila; Epithelial Cells; molekulární mimikry; myši; Humans; Bacterial Proteins; Mice; rozpustné proteiny pro vazbu faktoru citlivého k N-ethylmaleimidu; epitelové buňky; Soluble N-Ethylmaleimide-Sensitive Factor Attachment Proteins; zvířata; bakteriální proteiny; Animals; Host-Pathogen Interactions; Sequence Homology, Amino Acid; Molecular Mimicry; faktory virulence; Macrophages